2014
DOI: 10.1186/2193-1801-3-375
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic valve endocarditis due to Streptococcus pneumoniae

Abstract: IntroductionIn the pre-antibiotic era up 10% of cases of infective endocarditis were due to Streptococcus pneumoniae, but this association is currently exceedingly rare.Case descriptionSince 1997 we have diagnosed three patients, all aged >70, with endocarditis due to S. pneumoniae. One of these three cases involved a prosthetic valve, another a prosthetic ring. All three patients completely recovered with antibiotic treatment only.Discussion and evaluationDuring the same period there were 1694 cases of pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…TEE favors early detection of the disease and its complications and guides the appropriate therapeutic action throughout the clinical course. Given what has been reported to date , and the evolution of our patient, we would emphasize the need for intensive medical treatment and early surgery in patients with complications such as abscesses, large vegetations, or valve perforation, even when the SP is penicillin sensitive.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…TEE favors early detection of the disease and its complications and guides the appropriate therapeutic action throughout the clinical course. Given what has been reported to date , and the evolution of our patient, we would emphasize the need for intensive medical treatment and early surgery in patients with complications such as abscesses, large vegetations, or valve perforation, even when the SP is penicillin sensitive.…”
Section: Discussionmentioning
confidence: 87%
“…Another review of 16 patients with PE reported that the aortic and mitral valves were simultaneously affected in 4 cases (25%); these patients evolved satisfactorily, with medical treatment in two cases and combined medical–surgical treatment in the other two. Surgery was performed in 5 cases (31%) and 13 (81%) of the whole sample survived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation